Orbital frontal cortex functional connectivity during gain anticipation linking the rumination and non-suicidal self-injury in late adolescence - Lin, Lin; Liu, Yu; Qiu, Shaojie; Yang, Yanan; Yang, Yang; Tian, Mingyangjia; Wang, Song; Zhang, Jie; Bai, Xuejun; Xu, Zhansheng (Journal of affective disorders, 2024)
Non-suicidal self-injury (NSSI) is prevalent and especially among the adolescence population. It has been argued that abnormal brain activations in reward processing could be regarded as objective biomarkers in NSSI, but the evidence is mixed. This study aims to explore the reward processing mechanism of NSSI from the perspective of functional brain circuitry and investigate the role of a cognitive factor (rumination). Seventy-one 17–21 years old participants performed a monetary incentive delay (MID) task during functional magnetic resonance imaging scanning. Psychophysiological interaction (PPI) analysis was used to test the inner-group differences of brain functional connectivity. In addition, a mediation model was established with the mediation effect of rumination on the relationship between functional brain circuitry and NSSI. PPI analysis suggested that functional connectivity of the orbital frontal cortex (OFC) (with precuneus, SMA) was significantly enhanced in NSSI in the gain > loss contrast, but not in the loss > gain contrast. Mediation analysis revealed that rumination mediated the relationship between NSSI and the OFC- precuneus functional connectivity in the gain > loss contrast. Our research revealed that the abnormal OFC functional connectivity in gain (not loss) anticipation can be served as the sensitive biomarkers of NSSI. And there was a chain path for NSSI, that was from functional brain circuitry to negative cognition and then to problem behavior. •PPI seeds of gain and loss anticipation was independently explored by using task-related fMRI with a large sample.•The neural mechanism of NSSIs’ reward processing deficits was elaborated from the perspective of functional connectivity.•OFC, as the hub of multi-information integration, has an important influence on NSSI in gain anticipation.•Both rumination and OFC- precuneus functional connectivity were taken into consideration to find a chain path for NSSI.